1996
DOI: 10.1021/la9605798
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Kinetics of C12E8 at the Air−Water Interface:  Adsorption onto a Clean Interface

Abstract: The adsorption of C12E8 onto a clean air-water interface is studied by using a video-enhanced pendant bubble tensiometry. The controlling mechanism for mass transfer changes as a function of bulk concentration; it shifts from diffusion control at dilute concentration to mixed diffusion-kinetic control at more elevated bulk concentration. The adsorption of C 12E8 is found to be anticooperative from the equilibrium surface tension data compared with the prediction of the (generalized) Frumkin model. Relaxation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
151
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(177 citation statements)
references
References 26 publications
25
151
1
Order By: Relevance
“…Surface tension values measured for the air-water interface agree well with values reported in the literature. 41 Values of the CMC obtained from both air-water and oil-water surface tension measurements are in good agreement, as expected. To ensure that the surface tension has reached an equilibrium value, we also measure the interfacial tension after 12 h and we observe very little change.…”
Section: -3supporting
confidence: 84%
“…Surface tension values measured for the air-water interface agree well with values reported in the literature. 41 Values of the CMC obtained from both air-water and oil-water surface tension measurements are in good agreement, as expected. To ensure that the surface tension has reached an equilibrium value, we also measure the interfacial tension after 12 h and we observe very little change.…”
Section: -3supporting
confidence: 84%
“…that the data given in (15) for C 12 EO 8 are in satisfactory agreement with those presented in (13,17) only in the concentration range above 3 × 10 −6 mol/L. For lower concentrations the values given in (15) (not shown in Fig.…”
Section: Fig 2 the Same As Insupporting
confidence: 81%
“…1 and 2 for a broad range of n C (13,16,17). For some compounds, data from different authors are presented, which are in good mutual agreement.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…On the other hand, Lin et al (30,31) in studies on polyoxyethylene alcohols in air/water systems concluded that the controlling mechanism for mass transfer can change from diffusion to mixed kinetic-diffusion control as a function of bulk concentration. By examining how D changes with concentration they suggested a diffusion-controlled mechanism at dilute bulk concentrations, where the equilibrium surface coverage is low, and a mixed kinetic-diffusion control as the bulk concentration becomes higher and the equilibrium surface coverage is increased.…”
Section: Dynamic Interfacial Tensionmentioning
confidence: 99%